Jewish Mourning Rites—A Process of Resocialization - Fishbane, Simcha (Anthropologica, 2022)
This article is based on fieldwork among members of an Orthodox Jewish Congregation in North America. The author examines contemporary Jewish death and mourning rituals with particular attention to the duties and rights of the deceased's surviving kin. The latent (but sometimes overt) function of such rituals is to re-integrate the survivors into the religious community so that they may become active participants in it. The social facts thus outlined are an excellent illustration of the body of theoretical knowledge developed by Van Gennep and by Durkheimians past and contemporary (Hertz and Mary Douglas).